Global convergence analysis of the aggregate constraint homotopy method for nonlinear programming problems with both inequality and equality constraints. (3rd August 2018) - Zhou, Zhengyong; Su, Menglong; Shang, Yufeng; Wang, Fenghui
Abstract: In this paper, we construct appropriate aggregate mappings and a new aggregate constraint homotopy (ACH) equation by converting equality constraints to inequality constraints and introducing two variable parameters. Then, we propose an ACH method for nonlinear programming problems with inequality and equality constraints. Under suitable conditions, we obtain the global convergence of this ACH method, which makes us prove the existence of a bounded smooth path that connects a given point to a Karush–Kuhn–Tucker point of nonlinear programming problems. The numerical tracking of this path can lead to an implementable globally convergent algorithm. A numerical procedure is given to implement the proposed ACH method, and the computational results are reported.